Description of two extraordinary new species of freshwater stingrays of the genus Potamotrygon endemic to the rio Tapajós basin, Brazil (Chondrichthyes: Potamotrygonidae), with notes on other Tapajós stingrays - Carvalho, Marcelo R. De (Zootaxa, 2016)
Stingrays from the rio Tapajós basin are reviewed based on material collected from its lower (i.e. from the mouth-lake to Itaituba), middle (from about the São Luiz rapids to the confluence of rios Juruena and Teles Pires), and upper (above the Juruena-Teles Pires confluence) segments. Two new species endemic to the mid and upper Tapajós, discovered long ago and common in the ornamental fish trade, are described. Potamotrygon albimaculata sp. nov. is part of the black stingray species group, and is diagnosed by its blackish brown dorsal disc color with numerous and generally evenly-spaced small whitish spots and faint ocelli, multiple rows of thorns broadly spread on dorsal and lateral tail, pelvic fins with broadly rounded apices, and two angular cartilages with the posterior far more slender but about as wide as the anterior angular. Potamotrygon jabuti sp. nov. is diagnosed by its marbled color pattern that undergoes remarkable change with growth as adults have elaborate designs of beige, golden to yellowish-orange spots or ocelli surrounded by a slender beige to golden mesh-like pattern, but neonates have simple, well-separated ocelli; this species also has a single to double row of tail thorns varying in their development, monognathic heterodonty with teeth of intermediate lateral rows of upper jaws larger and hexagonal, and two robust, more or less equally developed angular cartilages. Both species co-occur in the relatively fast-flowing mid and upper Tapajós basin, but mostly occupy different areas of the river, with P. albimaculata sp. nov. more abundant in its central troughs but foraging at its margins, whereas P. jabuti sp. nov. is also present in smaller streams over rocky, sandy and leafy substrates. The Tapajós basin includes at least seven stingray species, but additional species probably also occur. Potamotrygon motoro, P. orbignyi, P. humerosa, Potamotrygon sp., and Paratrygon aiereba are present in the lower Tapajós mouth-lake, which may also include Plesiotrygon and Heliotrygon species. In addition to the new species described herein, P. orbignyi and Paratrygon cf. aiereba occur in the mid and upper Tapajós, along with another form (Potamotrygon cf. scobina) known only from the region of the São Luiz rapids. Therefore, three additional new species may be present in the Tapajós basin, which has one of the most diverse stingray assemblages known together with the rios Negro and Tocantins-Araguaia.